PERTANGGUNGJAWABAN PIDANA RUMAH SAKIT TERHADAP TINDAK PIDANA PEMALSUAN JUMLAH TAGIHAN UANG KEPADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) - Sonya Airini Batubara; Mazmur Septian Rumapea; Yusriando Yusriando (jurnal.unprimdn.ac.id, 2020)
PERTANGGUNGJAWABAN PIDANA RUMAH SAKIT TERHADAP TINDAK PIDANA PEMALSUAN JUMLAH TAGIHAN UANG KEPADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) sonyaairinibatubara@unprimdn.ac.id mazmursrumapea@unprimdn.ac.id Departemen Hukum Pidana, Fakultas Hukum, Universitas Prima Indonesia Jl. Sekip Simpang Sikambing, Medan, Sumatera Utara, 20112 Abstract Hospital is an institution that provides comprehensive health services that are preventive, promotive, curative and rehabilitative for the general public as stipulated in Article 1 paragraph (3) of Law Number 44 Year 2009 concerning Hospitals, which says